Analisis Produksi Padi Sawah (oryza sativa) di Nagari Batu Hampar Selatan Kecamatan Koto XI Tarusan Kabupaten Pesisir Selatan - Chairanisa Verina; Amnilis; Herda Gusvita (Jurnal Research Ilmu Pertanian, 2023)
The purpose of this study was to determine the characteristics of lowland rice farmers in Nagari Batu Hampar Selatan and to determine the effect of land area, labor costs, number of seeds, amount of pesticides, and amount of fertilizer. This research was conducted in Nagari Batu Hampar Selatan, Koto XI Tarusan District, Pesisir Selatan Regency from October to November 2021. The population in this study was 52 who met the criteria (land area, farming experience and planting season January – March 2021). Determination of the location is done intentionally (purposive). The data used are primary and secondary data. The data analysis used is multiple linear regression analysis using the SPSS version 2020 program with the Cobb – Doughlass function. The results showed that the characteristics of lowland rice farmers in Nagari Batu Hampar Selatan were (a) The majority of farmers are aged 38-50 years with a total of 32 samples (61.54%), (b) farmers' education which is more dominant is junior high school as many as 29 samples (55.76%). (c) the most dominant land area is 0.5 Ha as many as 41 samples (78.84%), (d) the number of family members is more dominant is 4-9 family members as many as 51 samples (98.08%), (e) land ownership status is entirely self-owned as many as 52 samples (100%). The production factor that has a significant effect on the amount of lowland rice production partially is the number of seeds (X3). Meanwhile, simultaneously (together) all production factors such as land area (X1), labor (X2), number of seeds (X3), amount of pesticides (X4), and amount of fertilizer (X5), have a significant effect on the amount of lowland rice production. . The coefficient of determination (R2) in this study was 79.5%, (variables of land area, labor costs, number of seeds, amount of pesticides and amount of fertilizer contributed 79.5% to production)